Micro-narratives in Amauta. Monthly journal of doctrine, literature, art, polemics - Vásquez Guevara, Erick Rony (2021)
The object of this research is to study the journal Amauta, as a disseminating organ of literary avant-gardism, and its objective is to propose the reading of some microtexts (“Fratricidio”, by Luis E. Valcárcel; “Alba”, by María Wiesse; and “Parábolas del Ande”, by Nazario Chávez Aliaga) published in its pages as micro-narratives. This study will focus on the microtexts and will analyze those that reveal a dominant narrative. From the description of the microtexts, it will be noted whether they meet the main characteristics of micro-narratives: brevity, narrativity and fictionality. As a consequence, it is suggested that some of these publications can be read as micronarratives.